Heat energy modelling of travelling wave piezoceramic ultrasonic motor - Mohd Fathuddin, Mohd Sunif; Mohd Noor Firdaus, Haron; F. R. M., Romlay (EDP Sciences, 2018)
This paper presents the method of determining and characterizing of a piezoelectric stator profile that applying in a piezoceramic ultrasonic motor with the consideration of heat generated. The piezoceramic ultrasonic motor is driven by the vibration of the piezoelectric element in order to ignite a motion. The harmonic and transient analysis of finite element method are used to predict the optimise operation frequency of the motor travelling wave. Then, a thermal analysis is conducted in order to analyse the heat distribution on the stator. The stator profile displacements with the variable temperature; 300, 360 and 450 K are analysed. The piezoceramic ultrasonic motor shows different longitudinal deflection with the increment of the temperature. Travelling wave optimization was found to be strongly dependent on the heat that generated by the piezoceramic.